Pengaruh Brand Image, Promotion, Dan Persepsi Harga Kepada Keputusan Pembelian Tiket Pesawat Terbang Pada Aplikasi Traveloka (Studi Kasus Pada Mahasiswa Bali Di Kota Malang ) - Putri, Hernita Cahyani Dwi; Basalamah, Muhammad Ridwan; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine the influence of Brand Image, Promotion, and Price Perception on the Decision to Purchase Flight Tickets on the Traveloka Application. The population in this study is Imade. The sampling method used in this research is the Likert scale method, by distributing questionnaires to respondents. This study involves 134 respondents. The research employs multiple linear regression analysis. The brand image variable has a partial effect on the decision to purchase flight tickets on the Traveloka application. The promotion variable has a partial effect on the decision to purchase flight tickets on the Traveloka application. The price perception variable has a partial effect on the decision to purchase flight tickets on the Traveloka application. Simultaneously, brand image, promotion, and price perception influence the decision to purchase flight tickets on the Traveloka application. Keywords: Brand Image, Promotion, Price Perception and Buying Decision